Pengembangan E-Book Interaktif Berbasis Flipbook Digital dalam Meningkatkan Keterampilan Menulis Siswa Kelas X MA Al I’dadiyyah Bahrul Ulum Tambakberas Jombang - Umi Unzilatur Rohmah; Aufia Aisa (Lembaga Yasin AlSys, 2025)
Arabic writing instruction for Grade X students at Madrasah Aliyah Al-I’dadiyyah Bahrul Ulum Tambakberas Jombang has remained predominantly conventional, relying on lectures and textbook-based exercises. This approach limits student engagement and hinders their ability to compose Arabic sentences independently. This study aims to develop, assess the feasibility of, and evaluate the effectiveness of a digital flipbook-based interactive e-book as a learning medium to enhance students’ writing skills. The method used is Research and Development (R&D) following the ADDIE model (Analysis, Design, Development, Implementation, Evaluation). Data collection techniques included interviews, questionnaires, observation, and pretest-posttest assessments. Validation results indicated a very high level of feasibility, with scores of 95% from the subject matter expert, 100% from the media expert, and 96% from students. Effectiveness testing using a Paired Sample t-Test yielded a significance value of 0.00 (p < 0.05), indicating a significant improvement in students’ writing skills following the use of the interactive e-book. The medium proved effective in enhancing learning interest, active participation, and students’ ability to write progressively and independently. The development of this interactive e-book offers an innovative and accessible learning tool, aligned with the demands of digitalized education and capable of overcoming the limitations of conventional methods.